The reception of the thought of Freud in the work of Ramon y Cajal - Rusiñol-Estragués, Jordi (2003)
If we analyzed the trajectory of these two great personalities we can appreciate common interests. Both study medicine and they are interested in the physiology of the nervous system. Both, hypnotism and its suggestion cause a great impression in these two scientists. Freud practiced hypnotism during its return to Vienna and Cajal used it with his patients in Valencia. Cajal does not accept the Freudians interpretations of the dreams. Besides the differences in the analysis of the dreams, the psychology of Freud and Cajal explain mental life in a very different ways.